The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/03635465221098141
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Trends in Meniscal Pathology in the Setting of Concomitant ACL Injuries in Pediatric and Young Adult Patients: An Insurance Database Study

Abstract: Background: Meniscal pathology is commonly encountered in the setting of anterior cruciate ligament (ACL) rupture and is increasingly common in the pediatric and adolescent population. Studies have shown that over half of individuals presenting with ACL rupture will have concurrent meniscal pathology. Purpose: To define trends in the utilization of meniscal procedures (ie, meniscus repair vs partial meniscectomy) and short-term complications in pediatric and young adult patients with meniscal pathology in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Jackson et al reported that boys were significantly more likely to have lateral meniscal tears and girls were significantly more likely to have medial meniscal tears. Other studies have reported that male patients had higher odds of undergoing concomitant meniscal procedures 4,24 ; however, the authors of those studies did not analyze the rates of medial versus lateral meniscal procedures separately. These sex-based differences between the 2 cohorts, specific to the tibial compartment, make future investigations of pediatric and adolescent patients particularly important.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Jackson et al reported that boys were significantly more likely to have lateral meniscal tears and girls were significantly more likely to have medial meniscal tears. Other studies have reported that male patients had higher odds of undergoing concomitant meniscal procedures 4,24 ; however, the authors of those studies did not analyze the rates of medial versus lateral meniscal procedures separately. These sex-based differences between the 2 cohorts, specific to the tibial compartment, make future investigations of pediatric and adolescent patients particularly important.…”
Section: Discussionmentioning
confidence: 98%
“…15,17 Isolated injury to the ACL is less common, 43 and associations with concomitant injury to the menisci have been well established, particularly in younger patient cohorts. 4,12,19,29,31,41 In addition to the increasing rates of pediatric ACL injury, the rates of concomitant meniscal surgeries have been likewise increasing. 4,12 Compared with adults, pediatric patients tend to have better outcomes after meniscal repair, which have been attributed to enhanced vascularity and healing potential.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of cruciate ligament injuries (CLI) has significantly increased in the past two decades, particularly among children and adolescents, due to increased sports participation (1-5). Additionally, there has been a recent sharp rise in anterior cruciate ligament (ACL) reconstruction among patients younger than 15 years old (4,6). While CLI epidemiological investigation in children and adolescents has been thoroughly researched in Europe and the United States (2,3,7,8), it remains under-researched in Asian countries, particularly China.…”
Section: Introductionmentioning
confidence: 99%
“…5 At the time of ACLR, 57% of adolescents also undergo meniscal surgery, which can complicate the rehabilitation process. 2 The menisci play a critical role in knee joint loading and dispersion of forces through the knee during dynamic activities. 11,12 Unfortunately, meniscal pathology can lead to joint instability, progressive reduction in joint space, and articular cartilage pathology.…”
mentioning
confidence: 99%